The relationship of nurse characteristics with prevention behavior and control of pulmonary tuberculosis infection - Sukartini, Tintin (Foundation for Enviromental Protection and Research, 2020)
Nurses who work in the Tuberculosis (TB) room are at great risk of contracting the disease. This study aimed to analyze the relationship of nurse characteristics with the prevention behavior and control of Tuberculosis infection. This research used a cross-sectional design. The population was all the nurses who work in the TB room. The number of the population taken was 40 respondents who have met the inclusion criteria. The dependent variable was the prevention behavior and control of Tuberculosis infection, while the independent variable was the nurse characteristics. The data were taken using questionnaires and observations towards nurses. Then, the data were analyzed using Chi-Square. The result showed no relation between education level with prevention behavior and tuberculosis infection (p=0.525). Training has no relation with the prevention behavior and control of tuberculosis infection (p=0.316). Working time has no relation to the prevention behavior and control of tuberculosis infection (p=0.190). Knowledge has no relation with the prevention behavior and control of tuberculosis infection (p=0.798). Attitude and motivation have no relation with the prevention behavior and control of tuberculosis infection (p=1.000). It can be concluded that there is no relation between nurse characteristics and prevention behavior and control of tuberculosis infection. The nurse behavior has implemented four pillars of prevention behavior and control of tuberculosis infection. Further research is suggested to research things related to the prevention behavior and control of tuberculosis infection such as compliance, workload, and self-efficacy of nurses.